Slovenska literatura na avstrijskem Koroškem - Leben, Andrej (Jezik in slovstvo, 2013)
The contribution sheds light on conceptual changes in the treatment and designation of Slovenian literature in Austrian Carinthia, both within the discourse of literary science and on the part of literary authors, on the backdrop of the sociopolitical contexts and literary development of the past decades. Recent literary practices, in particular, demonstrate that ethnic, linguistic and geographical criteria are inadequate for a comprehensive definition of the subject, especially in light of the fact that the literature of Slovenian authors in Carinthia ranges from Slovenian writings via hybrid language forms to writings in German and other languages. At the same time, literary images of the reality and space concerning the past and present of Carinthian Slovenes are also being created by authors who do not belong to a minority.
Keywords: slovenska zamejska književnost; regionalna književnost; narodne manjšine; avstrijska Koroška; Carinthia; literarna veda; literary science; dikurz